KEPEMIMPINAN BERDASARKAN DHARMA DALAM TEKS KAKAWIN BRAHMANDA PURANA - I Made Suweta (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2019)
Literary works become an inseparable part in the journey of culture and civilization of human creation itself. One such work is Kakawin Brahmanda Purana. The values of dharma and leadership in Kakawin Brahmanda Purana should be used as guidelines in life. Based on this background, there are important issues that will be discussed in this paper, namely how the dharma teachings in Hindu leadership in Kakawin Brahmanda Purana? The method used in this paper is the literature method and refer to the data discovery method. In writing using qualitative narrative techniques. Based on studies conducted, it can be found that the teachings of dharma in the story of Brahmanda Purana should be made learning for a leader, so that from his leadership can prosper the people and in accordance with the rules of dharma. Good behavior must be done by everyone, especially for a leader, because the leader will be a role model, an example, and an example for those they lead. The community will prosper if the leaders behave properly according to the teachings of their respective religions.